PERAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN KARAWANG DALAM TAHAP PENCEGAHAN DAN KESIAPSIAGAAN - Sunarti, Indriyani; Aryani, Lina (Jurnal Ilmiah Wahana Pendidikan, 2024)
In increasing public awareness in disaster management, BPBD Karawang Regency carries out disaster mitigation and prevention activities in areas that have a high level of vulnerability. The aim of this research is to explain and describe the process of community empowerment in disaster risk reduction. Based on the results of research on the role of BPBD Karawang Regency in prevention and preparedness, it has been able to provide services, assistance and solutions to people affected by disasters.Role, Prevention, Preparedness